Air stable organic-inorganic perovskite nanocrystals@polymer nanofibers and waveguide lasing - Wang, Zhe (2020)
Organic-inorganic hybrid perovskites have been considered as promising gain materials for lasing. Despite previous reports of lasing from nanocrystals, thin films and single crystals, the stability of perovskite lasers has been a challenge for its practical applications. Herein, a scalable strategy to prepare ultrastable perovskite@polymer hybrid fibers by employing a facile emulsion electrospinning approach is demonstrated. During the electrospinning process, polymethyl methacrylate (PMMA) first solidifies into an outer shell layer. Meanwhile, emulsion drops containing poly(vinylidene fluoride) (PVDF) and perovskite precursor are pushed inward and evolve into perovskite nanocrystals covered by PVDF. The PMMA with smooth surface benefits the light transport and the water-resistant PVDF blocks the moisture. The methylammonium lead bromide perovskite-embedded fibers can emit intensive light after storage in humid ambient environment (relative humidity >60%) or even in water. Amplified spontaneous emissions from the fibers network and waveguide lasing from chopped single fiber is demonstrated.